2017
DOI: 10.1088/1361-6463/aa59d3
|View full text |Cite
|
Sign up to set email alerts
|

Element-specific density profiles in interacting biomembrane models

Abstract: Surface interactions involving biomembranes, such as cell-cell interactions or membrane contacts inside cells play important roles in numerous biological processes. Structural insight into the interacting surfaces is a prerequisite to understand the interaction characteristics as well as the underlying physical mechanisms. Here, we work with simplified planar experimental models of membrane surfaces, composed of lipids and lipopolymers. Their interaction is quantified in terms of pressure-distance curves using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The influence of a variation of the parameters z 0 and w on the calculated curves is illustrated in the Supporting Information. As already discussed in our previous studies, 34,35 SWXF is sensitive mainly to the first and second moments of an elemental distribution. In other words, a similar fit quality would result from the assumption of a box-like elemental distribution as long as it has the same center-of-mass position and the same second moment σ 2 = ⟨(z − z 0 ) 2 ⟩ = w 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…The influence of a variation of the parameters z 0 and w on the calculated curves is illustrated in the Supporting Information. As already discussed in our previous studies, 34,35 SWXF is sensitive mainly to the first and second moments of an elemental distribution. In other words, a similar fit quality would result from the assumption of a box-like elemental distribution as long as it has the same center-of-mass position and the same second moment σ 2 = ⟨(z − z 0 ) 2 ⟩ = w 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…In the future, valuable experimental data on brush conformations can be expected from element-specific structural investigations, 50 which are sensitive, for instance, to the endpoint-distributions in interacting brushes. 24…”
Section: Discussionmentioning
confidence: 99%
“…23 Via controlled dehydration our double-monolayer configuration enables the tunable approach of the two surfaces and the separation-dependent structural investigation. 24 The monolayers are composed of lipids and lipopolymers ( Fig. 1A), supported by a hydrophobized planar solid on one side, but free-standing on the other side ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In situ and real-time GIXF and GID study of the structural rearrangement in a model membrane (an arachidic acid monolayer) on a colloidal solution of cerium dioxide or magnetite showed that the character of the interaction of nanoparticles with the monolayer is determined by their chemical nature and size [172]. The interaction of membrane surfaces composed of lipids and lipopolymers was quantified at controlled dehydrating pressures using GIXF [173]. This technique yielded specific density profiles of the chemical elements P and S belonging to lipid headgroups and polymer chains, as well as counterion profiles for charged surfaces.…”
Section: Model Biological Membranesmentioning
confidence: 99%